Integration of Mitochondrial Targeting for Molecular Cancer Therapeutics - Philippe Marchetti; Pierre Guerreschi; Laurent Mortier; Jerome Kluza (International Journal of Cell Biology)
Mitochondrial metabolism greatly influences cancer cell survival, invasion, metastasis, and resistance to many anticancer drugs. Furthermore, molecular-targeted therapies (e.g., oncogenic kinase inhibitors) create a dependence of surviving cells on mitochondrial metabolism. For these reasons, inhibition of mitochondrial metabolism represents promising therapeutic pathways in cancer. This review provides an overview of mitochondrial metabolism in cancer and discusses the limitations of mitochondrial inhibition for cancer treatment. Finally, we present preclinical evidence that mitochondrial inhibition could be associated with oncogenic “drivers” inhibitors, which may lead to innovative drug combinations for improving the efficacy of molecular-targeted therapy.